Division E Commission 10: Solar activity - Schrijver, Carolus J. (2016)
After more than half a century of community support related to the science of "solar activity", IAU Commission 10 was formally discontinued in 2015, to be succeeded by C.E2 with the same area of responsibility. On this occasion, we look back at the growth of the scientific disciplines involved around the world over almost a full century. Solar activity and fields of research looking into the related physics of the heliosphere continue to be vibrant and growing, with currently over 2,000 refereed publications appearing per year from over 4,000 unique authors, publishing in dozens of distinct journals and meeting in dozens of workshops and conferences each year. The size of the rapidly growing community and of the observational and computational data volumes, along with the multitude of connections into other branches of astrophysics, pose significant challenges; aspects of these challenges are beginning to be addressed through, among others, the development of new systems of literature reviews, machine-searchable archives for data and publications, and virtual observatories. As customary in these reports, we highlight some of the research topics that have seen particular interest over the most recent triennium, specifically active-region magnetic fields, coronal thermal structure, coronal seismology, flares and eruptions, and the variability of solar activity on long time scales. We close with a collection of developments, discoveries, and surprises that illustrate the range and dynamics of the discipline.